Artificial Ground Motions and Nonlinear Response of RC Structures - Marco Filippo Ferrotto; Francesco Basone; Panangiotis G. Asteris; Liborio Cavaleri (Advances in Civil Engineering)
The selection of seismic inputs for nonlinear dynamic analysis is widely debated, mainly focusing on the advantages and disadvantages provided by the choice of natural, simulated, or artificial records. This work proves the differences in the structural behavior of RC buildings when using accelerograms with different levels of stationarity. Initially, nonlinear response under three sets of accelerograms equivalent in terms of pseudo acceleration spectrum is evaluated and compared. Then, the results of incremental dynamic analyses are compared by the statistical point of view considering different levels of irregularity for the reference structure.